Development of patient-centred standards of care for rheumatoid arthritis in Europe: the eumusc.net project. Issue 5 (6th August 2013) - Stoffer, Michaela A; Smolen, Josef S; Woolf, Anthony; Ambrozic, Ales; Bosworth, Ailsa; Carmona, Loreto; Fialka-Moser, Veronika; Loza, Estibaliz; Olejnik, Pawel; Petersson, Ingemar F; Uhlig, Till; Stamm, Tanja A; et al.
Abstract : Objective: The eumusc.net project is a European Union (EU) commission and European League Against Rheumatism (EULAR)funded project that aims to facilitate equal standards for musculoskeletal health in all EU countries. One work-package was to develop evidence-based and patient-centred standards of care (SOC), for rheumatoid arthritis (RA) understandable for patients and professionals across Europe. Method: A review of documents covering clinical practice 'guidelines' and SOC for RA was conducted. The obtained documents were evaluated using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) criteria, and all recommended methods to treat RA were extracted. Based on this information, a three-round Delphi exercise was performed including a consensus group meeting of 21 researchers and patient representatives. Results: 16 patient-centred SOC were formulated including a lay version in the format of a checklist. An example is SOC 3: 'People with RA should receive a treatment plan developed individually between them and their clinician at each visit.' The corresponding checklist question reads: 'Have I received a treatment plan which includes an explanation of my management, expected goals and outcomes and important contact details?' Conclusions: The SOC for RA will be available in all 23 official European languages and contribute to more unified treatment approaches in Europe.